Growth kinetics of Salmonella abortus equi infection in C57BL/6 mice - Tirpude, R J; Kumar, Pradeep; Batra, H V; Malhotra, P R; Kaul, R K; Pandya, G (The Indian Journal of Animal Sciences, 2012)
Mouse protection test is the method of choice for evaluating the potency of a given vaccine where the bacterial challenge dose and route of administration play a crucial role. In this study therefore, bacterial growth kinetics of Salmonella abortus equi was studied in susceptible inbred C57BL/6 mice in liver and spleen by different routes. Results indicate that the peak bacterial growth was evident by intravenous route by day 5 post infection (PI) in both liver (16.37 Â± 2.65 x 10â¶ CFU) and spleen (5.87 Â± 1.52 x 10â¶ ). A sharp decline in bacterial growth was detected after day 10 PI. Subcutaneous route showed a lower bacterial growth kinetics whereas oral route indicated the lowest bacterial growth. However, the pattern of sustaining the bacterial growth in terms of time schedule was consistent with the intravenous route.